This is where we go: the quantum healing possibilities in languaging Black humanity - Afolalu, Lakeya; Smith, Patriann; Austin, Tasha (My University, 2026)
Homogenizing narratives dehumanize racially minoritized groups while obscuring the mechanisms and structures of white supremacy that ultimately harm everyone. Through an intimate conversation, Black women scholars from African American, Caribbean, and African backgrounds, the paper aims to thicken solidarities across Black diasporic difference. By exploring intraracial overlaps and tensions, this dialogue disrupts narratives that flatten Black diasporic identity diversity, erase Black global linguistic varieties, and silence varied Black histories. In turn, the conversation reveals that authentic solidarity emerges from honoring intracultural nuances, confronting internalized colonial logics, and centering youth voices alongside intergenerational knowledge. Design/methodology/approach This conversation formalized years of informal discussions among three Black diasporic women scholars. Grounded in established trust and our positionalities, the dialogue flowed organically in response to open-ended questions that enabled the authors’ distinct rhetorical and cultural traditions to emerge. In doing so, the authors embodied the very linguistic practices they analyzed by transgressing academic rhetoric to speak in various Black global languages. The authors’ linguistic fidelity honors Black feminist and transnational epistemologies, emphasizes relational knowledge production, and offers a rhetorical illustration of solidarity-building in practice. Findings While the authors’ dialogue defies traditional ‘findings,’ key themes emerged. Thickening Black diasporic solidarities requires confronting internalized colonization and moving beyond divisive reactions toward intraracial healing. Self-definition aids in healing generational trauma. Linguistic creativity, from Negro spirituals to digital literacies, are essential for collective integenerational resistance. Spiritual joy differs from externally imposed, performative happiness, and fear of professional/personal loss inhibits authentic solidarity work. Multicultural education must integrate Black linguistic diversity into teacher preparation programs in ways that transgress deficit framings. While racialization flattens Black heterogeneity, dialogues like this one function as critical spaces of refuge, fugitivity and diasporic healing. Originality/value The authors’ dialogue models the very solidarity it theorizes, as the authors speak and make meaning in Black languages while analyzing Black linguistic diversity. In doing so, the authors make visible intraracial tensions that homogenizing narratives erase and theorize dialogue as a refuge for Black women scholars navigating racialized violence. They center youth as generational innovators and demonstrate the necessity of confronting internalized colonization. This conversation emphasizes that solidarity arises from honoring intracultural differences. Insights from the authors’ conversation have implications for multicultural education across various learning spaces, including teacher preparation programs, classrooms and community- and youth-centered organizations.